A comprehensive meta-analysis of Brucella infections in aquatic mammals - Dadar, Maryam; Shahali, Youcef; Fakhri, Yadolah; Godfroid, Jacques (Veterinaria Italiana, 2022)
The presence of Brucella infections was documented in a large number of aquatic mammals, affecting wild animals living in oceans, seas, lakes and rivers within both northern and southern hemispheres. Through meta‑regression analysis, this study provides a comprehensive view of the prevalence of Brucella spp. in aquatic mammals, identifying risk subgroups as well as most common sampling and testing methods. Brucella ceti and Brucella pinnipedialis represent the main marine Brucella spp., with documented enzootic potential, for which information on standardized diagnostic methods for the implementation of efficient screening and monitoring programs is needed. A total of 71 articles investigating the occurrence of brucellosis in aquatic mammals since 1987, have met the inclusion criteria and have been included in this study. The prevalence of brucellosis in males (30.42%) was significantly higher than females (18.59%). The family of Delphinidae was the most studied among aquatic mammals with a total prevalence of 39.66%. Our meta‑regression analysis showed a strong and significant association between the prevalence of Brucella spp. in mammals and water temperature (C = 0.02, p value = 0.003), while no significant correlation was found with water salinity (C = ‑ 0.09; p value = 0.10). At least 130 species of aquatic mammals have been identified as potential hosts for Brucella spp. There is no systematic veterinary inspection and global or local requirements for the monitoring of brucellosis in aquatic mammals. The association of brucellosis prevalence and water temperature warrants further studies to assess the potential direct and indirect impacts of climate change on brucellosis in aquatic mammals. This study would help to determine the basis of adaptive management strategies in order to control enzootic brucellosis in wild aquatic mammals.